Taper angle optimization of scarf repairs in carbon-epoxy laminates - R. D. S. G. Campilho (2010)
The increasing use of Carbon-Fibre Reinforced Plastic (CFRP) laminates in high responsibility applications introducesan issue regarding their handling after damage. The availability of efficient repair methods is essential to restore thestrength of the structure. The availability of accurate predictive tools for the repairs behaviour is also essential for thereduction of costs and time associated to extensive tests. This work reports on a numerical study of the tensile behaviourof three-dimensional (3D) adhesively-bonded scarf repairs in CFRP structures, using a ductile adhesive. The FiniteElement (FE) analysis was performed in ABAQUS® and Cohesive Zone Models (CZMs) was used for the simulation ofdamage in the adhesive layer. A parametric study was performed on two geometric parameters. The use of overlaminatingplies covering the repaired region at the outer or both repair surfaces was also tested as an attempt to increasethe repairs efficiency. The results allowed the proposal of design principles for repairing CFRP structures.